Computational design and initial corrosion assessment of a series of non-equimolar high entropy alloys. (November 2019) - Lu, Pin; Saal, James E.; Olson, Gregory B.; Li, Tianshu; Sahu, Sarita; Swanson, Orion J.; Frankel, G.S.; Gerard, Angela Y.; Scully, John R.
Abstract: The integrated computational materials engineering approach has been employed to design a series of four single-phase non-equimolar high entropy alloys (HEAs) with systematically varied compositions (Ni38 Fe20 Crx Mn21–0.5x Co21–0.5x with x = 6, 10, 14, and 22) and corrosion behavior. The HEAs were successfully designed, synthesized and confirmed to possess a single-phase FCC structure. Preliminary electrochemical corrosion characterization was conducted to gain fundamental understanding of the effects of HEA composition on corrosion resistance, which will be utilized to develop mechanistic corrosion models that enable the optimal design of corrosion resistant HEA. HEA containing 6 at.% Cr showed indications of passivity at a relatively low Cr content. Graphical abstract: Unlabelled Image